STUDENTS’ PERCEPTION TOWARD THE USE OF ENGLISH SONG FOR SPEAKING SKILL - Pandey, Apriliyane; Hampp, Paula; Andries, Fivy (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The aim of this research is to identify the perceptions of students about the use of song for speaking skill. The researcher used questionnaire in this research. The researcher used descriptive method which is survey method to analyze the data. Survey method was used to analyze the data directly from people. The population of this research were the third grade students of SMA Negeri 1 Tomohon. There were 10 classes that divided into 5 science classes, 3 social classes, and 2 language & culture classes. There were 297 students of third grade at the school. The sample was 15% of the population and the researcher used simple random technique. In other words, there were 44 students participated in this research. Based on the findings of the research, it was found that the students as the sample had a great deal in experience by using song, and the perception from the questions were dominated positively. The conclusion was the use of song considered to be beneficial and effective for third grade students of SMA Negeri 1 Tomohon. It was suggested to English teachers to always improve the way of teaching, monitoring the improvement of technology that can be improved things especially in learning speaking and gain the benefits from the result.